SPENDING THE FREE TIME OF STUDENTS PROFESSIONALLY, IMPROVING THEIR ENTREPRENEURIAL SKILLS AND PROVIDING SOCIAL SUPPORT TO THEM - Orinbaeva Khilola Avazovna (American Journals, 2022)
This article talks about the modern conditions and opportunities created for students to spend their free time productively, get an education, acquire a profession, improve entrepreneurship skills and provide them with social support.
Keywords: information technologies, conditions and opportunities, meaningful, economic reforms, investment